The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00339-009-5228-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterisation of microscale air bridges in conductive gallium nitride

Abstract: Fabrication and electrical characterisation of microscale air bridges consisting of GaN heavily doped with silicon is described. These were made from GaN-AlInN-GaN epitaxial trilayers on sapphire substrates, in which the AlInN was close to the composition lattice matched to GaN at ~17% InN fraction. The start of the fabrication sequence used inductively coupled plasma etching with chlorine chemistry to define mesas. In situ monitoring by laser reflectometry indicated an AlInN vertical etch rate of 400 nm/minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The second type of microstructure consisted of rectangular beams 4 μm wide by 20 μm in length each supported between two larger square anchor posts. The planview geometry was the same as that used to fabricate singlelayer doped GaN microbridges for electrical studies reported in [13]. Figure 3(a) shows an oblique SEM image of a microstructure containing two AlInN layers, which have been exposed by vertical ICP etching, but not yet subjected to wet etching.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second type of microstructure consisted of rectangular beams 4 μm wide by 20 μm in length each supported between two larger square anchor posts. The planview geometry was the same as that used to fabricate singlelayer doped GaN microbridges for electrical studies reported in [13]. Figure 3(a) shows an oblique SEM image of a microstructure containing two AlInN layers, which have been exposed by vertical ICP etching, but not yet subjected to wet etching.…”
Section: Resultsmentioning
confidence: 99%
“…to form resonant cavity light-emitting diodes) and microcavities. Also wider applications of the sacrificial layer technology are expected in fabrication of microelectromechanical sensors and actuators [4,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HEATE method can be implemented with a simple equipment configuration, and the thin SiO 2 mask enables ultrafine nanofabrication that is tens of nanometers in size. Membrane structures that require strong optical confinement are commonly used for PhCs, and several fabrication techniques such as Si-selective dry etching for GaN/Si structures, 25) photoelectrochemical wet etching of InGaN superlattice sacrificial layers, 26) selective high-temperature pyrolysis of GaN for AlGaN/GaN structures, 27) and selective wet etching of AlInN sacrificial layers by hot nitric acid [28][29][30][31][32][33] have been reported.…”
Section: Introductionmentioning
confidence: 99%